The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4025/actascibiolsci.v40i1.36330
|View full text |Cite
|
Sign up to set email alerts
|

<b>Fish parasite diversity in the Amambai river, State Mato Grosso do Sul, Brazil

Abstract: This study aimed to describe the diversity of fish parasites in the Amambai River, in the Mato Grosso do Sul State, and generate information to facilitate studies of the biotic integrity of the region. During the period of September 2015 and July 2015, 48 specimens of 11 species of fish were analyzed for parasites. A total of 56.25% of the fish sampled from the Amambai River were infected with one or more metazoan species. A total of 21,514 parasite specimens belonging to 24 different species we found; they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Fish of wild populations have a more diversified diet than those in manmade lakes and reservoirs, which can positively affect the composition of endoparasites because the diet can include numerous animals that act as intermediate and/or paratenic hosts (PEREIRA et al, 2018). In the present study, Capillariidae gen.…”
Section: Discussionmentioning
confidence: 73%
“…Fish of wild populations have a more diversified diet than those in manmade lakes and reservoirs, which can positively affect the composition of endoparasites because the diet can include numerous animals that act as intermediate and/or paratenic hosts (PEREIRA et al, 2018). In the present study, Capillariidae gen.…”
Section: Discussionmentioning
confidence: 73%
“…However, they added that the prevalence and mean intensity were Science and Management Volume 16 Number 4, June 2021: 75-84 recorded at 0.3 % and one per fish, respectively, which was the lowest value for a parasite species found in fish of Tonga Lake. On the other hand, Pereira et al (2018) found a 2.08% prevalence of Cucullanus sp. infestation in long-whiskered catfish (Sorubin lima) caught in the Amambai river in Brazil, which was a new parasite record for this host.…”
Section: Nematode Identification Prevalence and Mean Intensitymentioning
confidence: 92%
“…Hooks with ancyrocephaline distribution. Hooks similar in shape and size; point and shaft delicate, erect thumb, shank expanded, tapering abruptly proximally in a point, 15 (13)(14)(15)(16); n = 70); FH loop about 3/4 shank length.…”
Section: Descriptionmentioning
confidence: 99%
“…Currently, 23 species of Cosmetocleithrum are recognized as parasites of the gills of neotropical Siluriformes, among which 15 species recorded in doradids hosts, eight in Auchenipteridae, one parasitizing Pimelodidae, and one in Loricariidae. All species of Cosmetocleithrum have been described from hosts of members of a single family [1,4,5,15,22,23,24], except for Cosmetocleithrum bulbocirrus Kritsky, Thatcher & Boeger, 1986, reported from species of three different siluriform families and from Hoplias malabaricus (Bloch), a characiform fish [7]. However, considering that only one specimen was found in the latter host, this record needs to be confirmed.…”
Section: Introductionmentioning
confidence: 99%